DOMESTIKASI IDEOLOGI DALAM PENERJEMAHAN INJIL: INGGRIS-BALI - Frans I Made Brata Brata (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
The Bible’s translator expects his translation not only accurate, but also acceptable in accordance to the norms and cultural value of its reader. This study aims   to   describe   the   domesticating   ideology   in   translation.   Tu-VousTheory combined with Attitude, as part of Appraisal Theory in Systemic Functional Linguistics   are  used  to  investigate  how  the  word  should  be  used.  Dynamic Equivalence Theory is utilized to describe the word in use in society.   Descriptive qualitative   approach   in  determining   two   principle   orientations   of  translation techniques,   methods,   and   ideologies   were   applied   in   analyzing   the   data. Questionnaires containing sentences with English terms of address in Luke’s Bible and their equivalents in Balinese were used to verify the data. The findings show that  the domesticating  ideology  has  a positive  contribution  to the quality of the translation with regard to its accuracy, acceptability, and readability.